(untitled) (Eurasian Journal of Humanities and Social Sciences, 2021)
Artists invented the first pigments—a combination of soil, animal fat, burnt charcoal, and chalk—as early as 40,000 years ago, creating a basic palette of five colors: red, yellow, brown, black, and white. Since then, the history of color has been one of perpetual discovery, whether through exploration or scientific advancement. The invention of new pigments accompanied the developments of art history’s greatest movements—from the Renaissance to Impressionism—as artists experimented with colors never before seen in the history of painting